Role of Artificial Intelligence in Shaping Customer Satisfaction: A Systematic Literature Review and Bibliometric Analysis - Zabłocka-Kluczka, Anna; Sałamacha, Anna; Ropuszyńska-Surma, Edyta; Lipowski, Marcin (Rola sztucznej inteligencji w kształtowaniu satysfakcji klienta: systematyczny przegląd literatury oraz analiza bibliometryczna, 2025)
Aim: The purpose of this study was to provide a comprehensive assessment of the current state of knowledge about the role of artificial intelligence in shaping customer satisfaction, especially satisfaction with AI-based services and products. Methodology: To achieve this aim a literature review was conducted following the systematic literature review method, using the PRISMA guidelines. The bibliometric analysis and visual exploration of the literature review were carried out using VOSviewer software. Results: The research results allowed to conclude that over the last five years research into the application of artificial intelligence in the field of customer service and products has undergone a distinct evolution. Research is mainly on front-office activities, while the back-office activities are quite rarely discussed. Implications and recommendations: Due to its novelty, the interest in this topic is still growing and the number of publications will probably increase dynamically in the coming period. In order to discover the research gaps it is worth deepening the presented analyses by content analysis as the next step of the planned research. Originality/value: The literature review revealed the current state of research in the area, while identifying important cognitive gaps that may set potentially interesting directions for future scientific exploration.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 134-150
Keywords: artificial intelligence; customer satisfaction; systematic literature review; management; sztuczna inteligencja; satysfakcja klienta; systematyczny przegląd literatury; zarządzanie